Anthropological Crisis? Notes For A Critical Interpretation of The Anthropological Situation of Our Time - Fornet-Betancourt, Raúl (2014)
This article aims to draw attention to the central role that must have for us as human, existential and social beings to live an anthropological crisis. This crisis shows us that we, in our project of being humans, are in crisis. Not only our present world is in crisis; it is also, and mainly, our own human presence, our way of making our humanity present in the world, which is in crisis. These reflections have as background many philosophical analyses on the spiritual and/or cultural situation of humanity in the twentieth century and in the beginning of the current century.